Gender and Social Inclusion: Case study frameworks and indicators - Huyer, Sophia (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The presentation was made during the second AICCRA GSI workshop held in September 2021 and discusses the broad compenents of the two gender case studies. The first case study is related to women-targeted strategies to develop gender-responsive CSA. This includes understanding the role of women researchers and capacity development implementers in increasing the gender-responsiveness of CSA technologies; and the role of participatory approaches to CSA development and implementation in promoting gender-responsive CSA technologies and practices. The second case study aims to pomote women’s entry and advancement in agriculture and climate research, in terms of strategies to support women’s positive career experience and progression in AICCRA, including institutional family-work life strategies and mentoring: understanding strategies that were used to encourage participation of women, and the results from this participation.